Impacts of Heavy Metals and Behavioral Changes in Humans - Baig, Ayesha; Bin Saadat, Hassaan (Journal of Basic and Emerging Sciences, 2024)
Heavy metal pollution not only affects the environment but if absorbed into the body such as lead, mercury, cadmium and arsenic can accumulate in leading to a range of adverse health effects. Chronic exposure to heavy metals can result in long term health problem. Various behavioral changes are associated with heavy metals exposure such as depression, anxiety, irregular heartbeats, stress, decrease in strength and power, lack of confidence, restlessness, lack of tolerance and aggressions among the individuals and the society as a whole. This review entails the information regarding sources of heavy metals, exposure pathways and health effects of heavy metals resulting in behavioral changes in humans.